High-power lasers and applications IV : 12-14 November 2007, Beijing, China - High-Power Lasers and Applications Conference (4th : 2007 : Beijing); Fan, Dianyuan; Walter, Robert Frederick; Society of Photo-Optical Instrumentation Engineers (Washington : SPIE, 2008)
07